Freedom Research in Education Becoming an Autonomous Researcher - McArdle, Karen (Palgrave Studies in Education Research Methods,, 2018)
This book sets out a new and distinctive means of conceptualising research in the field of Education: 'Freedom Research'. Freedom research is a conceptual understanding of research free from the strictures of orthodoxy; which adapts or knowingly critiques conventions about the ways in which research should be conducted. Underpinning this concept is the argument that the conventions of traditional approaches to research in education may be both confidence-sapping and constrictive to both the early career and mature educational researcher. By critiquing the boundaries of a socially constructed discipline, the researcher may then be liberated to research with freedom, creativity and innovation. This pioneering volume will assist the researcher to become more autonomous, and by extension more confident, in their own research practice. It will be of appeal to scholars, students and researchers in Education, of all stages of their career. Karen McArdle is Professor Emerita at the University of Aberdeen, UK. She has been engaged in educational research for more than thirty years, primarily in the UK and Australia.